Zika virus transmission in Angola and the potential for further spread to other African settings - Kraemer, M; Brady, O; Watts, A; German, M; Hay, S; Khan, K; Bogoch, I (Oxford University Press, 2018)
Background Cases of Zika virus were recently detected in Luanda, Angola, a major travel hub in Africa. The risk of Zika virus transmission throughout the continent from Angola is evaluated. Methods Travel volumes were assessed using monthly passenger-level flight data from Luanda to all locations throughout Africa. Travel data was superimposed onto seasonal environmental suitability maps that predict the potential for subsequent Zika virus transmission. Results and Conclusions Windhoek, Maputo, Durban and Kinshasa have the greatest potential for Zika virus introduction and transmission during the southern hemisphere summer months, and Nairobi during the northern hemisphere summer months.